Re-analysis of RNA-seq transcriptome data reveals new aspects of gene activity in Arabidopsis root hairs - Li, Wenfeng; Lan, Ping (Frontiers in Plant Science, 2015)
Root hairs, tubular-shaped outgrowths from root epidermal cells, play important roles in the acquisition of nutrients and water, interaction with microbe, and in plant anchorage. As a specialized cell type, root hairs, especially in Arabidopsis, provide a pragmatic research system for various aspects of studies. Here, we re-analyzed the RNA-seq transcriptome profile of Arabidopsis root hair cells by Tophat software and used Cufflinks program to mine the differentially expressed genes. Results showed that, ERD14, RIN4, AT5G64401 were among the most abundant genes in the root hair cells; while ATGSTU2, AT5G54940, AT4G30530 were highly expressed in non-root hair tissues. In total, 5409 genes, with a fold change greater than 2-fold (FDR adjusted P<0.05), showed differential expression between root hair cells and non-root hair tissues. Of which, 61 were expressed only in root hair cells. 136 out of 5409 genes have been reported to be “core” root epidermal genes, which could be grouped into nine clusters according to expression patterns. Gene ontology (GO) analysis of the 5409 genes showed that processes of “response to salt stress”, “ribosome biogenesis”, “protein phosphorylation”, and “response to water deprivation” were enriched. Whereas only process of “intracellular signal transduction” was enriched in the subset of 61 genes expressed only in the root hair cells. 121 unannotated transcripts were identified and 14 of which were shown to be differentially expressed between root hair cells and non-root hair tissues, with transcripts XLOC_000763, XLOC_031361, and XLOC_005665 being highly expressed in the root hair cells. The comprehensive transcriptomic analysis provides new information on root hair gene activity and sets the stage for follow-up experiments to certify the biological functions of the newly identified genes and novel transcripts in root hair cell morphogenesis.